Pengaruh Fee Audit, Audit Tenure, dan Audit Delay Terhadap Kualitas Audit pada Perusahaan Sub Sektor Makanan dan Minuman - Agus Triya Nur Hasanah; Emilia Gustini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Thiis study aiiims to ainailyze the effect of aiudiit fees, aiudiit tenure, aind aiudiit delaiy on aiudiit quailiity iin food aind beveraige compainiies liisted on the Iindonesiiai Stock Exchainge for the 2021–2023 periiod. The reseairch aipproaich used wais quaintiitaitiive wiith multiiple liineair regressiion, usiing 32 compainiies ais saimples through ai purposiive saimpliing techniique, resultiing iin ai totail of 96 observaitiions. The t-test results iindiicaite thait aiudiit fees (t = 4,564 ; siig = 0.000) aind aiudiit tenure (t = 7,883 ; siig = 0.000) haive ai siigniifiicaint posiitiive effect on aiudiit quailiity, whiile aiudiit delaiy (t = -9,531 ; siig = 0.000) hais ai siigniifiicaint negaitiive effect. The Aidjusted R² vailue of 0,851 iindiicaites thait 85,1% of the vairiiaitiion iin aiudiit quailiity cain be explaiiined by the three iindependent vairiiaibles. Therefore, the aimount of aiudiit fees aind the length of the aiudiitor's relaitiionshiip wiith the cliient iincreaise aiudiit quailiity, whiile aiudiit delaiy aictuailly decreaises iit.